How women got their curves and other just-so stories : evolutionary enigmas - Barash, David P. (Columbia University Press, 2009)
"So how did women get their curves? Why do they have breasts, while other mammals only develop breast tissue while lactating, and why do women menstruate, when virtually no other beings do so? What are the reasons for female orgasm? Why are human females kept in the dark about their own time of ovulation and maximum fertility, and why are they the only animals to experience menopause? David P. Barash and Judith Eve Lipton, coauthors of acclaimed books on human sexuality and gender, discuss the theories scientists have advanced to explain these evolutionary enigmas (sometimes called "Just-So stories" by their detractors) and present hypotheses of their own. Some scientific theories are based on legitimate empirical data, while others are pure speculation. Barash and Lipton distinguish between what is solid and what remains uncertain, skillfully incorporating their expert knowledge of biology, psychology, animal behavior, anthropology, and human sexuality into their entertaining critiques. Inviting readers to examine the evidence and draw their own conclusions, Barash and Lipton tell an evolutionary suspense story that captures the excitement and thrill of true scientific detection."--Jacket.